Structural and functional distinctions of co-resident microglia and monocyte-derived macrophages after retinal degeneration - Kaitryn E. Ronning; Sarah J. Karlen; Marie E. Burns (Journal of Neuroinflammation, 2022)
Abstract Background Both resident microglia and invading peripheral immune cells can respond to injury and degeneration in the central nervous system. However, after dead and dying neurons have been cleared and homeostasis is re-established, it is unknown whether resident immune cells fully resume normal functions and to what degree the peripheral immune cells take up residence. Methods Using flow cytometry, in vivo retinal imaging, immunohistochemistry, and single-cell mRNA sequencing, we assess resident microglia and monocyte-derived macrophages in the retina during and after the loss of photoreceptors in the Arr1 −/− mouse model of inducible degeneration. Results We find that photoreceptor loss results in a small, sustained increase in mononuclear phagocytes and, after degeneration wanes, these cells re-establish a spatial mosaic reminiscent of healthy retinas. Transcriptomic analysis revealed the population remained unusually heterogeneous, with several subpopulations expressing gene patterns consistent with mildly activated phenotypes. Roughly a third of “new resident” cells expressed markers traditionally associated with both microglial and monocytic lineages, making their etiology ambiguous. Using an inducible Cre-based fluorescent lineage tracing paradigm to confirm the origins of new resident immune cells, we found approximately equal numbers of microglia and monocyte-derived macrophages after degeneration had subsided. In vivo retinal imaging and immunohistochemical analysis showed that both subpopulations remained functionally responsive to sites of local damage, though on average the monocyte-derived cells had less morphological complexity, expressed higher levels of MHCII, and had less migratory activity than the native resident population. Conclusions Monocytic cells that infiltrate the retina during degeneration differentiate into monocyte-derived macrophages that can remain in the retina long-term. These monocyte-derived macrophages adopt ramified morphologies and microglia-like gene expression. However, they remain distinguishable in morphology and gene expression from resident microglia and appear to differ functionally, showing less responsiveness to subsequent retinal injuries. These findings support the idea that persistent changes in the local immune population that occur in response to cell loss in aging and progressive retinal diseases may include the establishment of subpopulations of bone marrow-derived cells whose ability to respond to subsequent insults wanes over time.